OPTIMALISASI PRODUKTIVITAS UKM PERALATAN DAPUR DENGAN PENDEKATAN LEAN THINKING DAN EMPLOYEE BEHAVIOUR - Qurratu’aini, Nafia Ilhama; Taqwanur (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
UKM Gajah Delta is an SME engaged in the production of kitchen equipment, the main product of food containers with a lid section using several business locations that are far apart. manually operated machines and employees with low levels of education. These conditions have an impact on employee productivity that does not meet management expectations. Low productivity due to low personnel competence, lack of equipment, and no material handling. To improve this performance, the Lean Thinking method is used by identifying activities that do not add value (NVVA), and activities that add value (VAA). The tool used in Value Stream Analysis with the focus of improvement in Process Activity Mapping (PAM). The biggest waste occurs in transportation, unnecessary movement and employee behavior. From the focus group discussion, the root of the problem and proposed improvements were obtained based on the priority scale with the IUP Matrix, so the total production time for food container lids has improved to 784 seconds or 45.06%. The priority for employee behavior improvement actions is briefing activities before carrying out work activities, making employee work schedules, and improving competence through training